Free Market Criminal Justice : How Democracy and Laissez Faire Undermine the Rule of Law - Brown, Darryl K. (New York Oxford University Press, 2016)
Free Market Criminal Justice explains how excessive faith in democratic politics and free markets has undermined the rule of law in the US criminal process. It argues that, to strengthen the rule of law, American criminal justice needs less democracy, less market-inspired process, and more law.
Include Index
Keywords: United States -- Law and economics -- Plea bargaining